SISTEM PENDUKUNG KEPUTUSAN DIAGNOSIS GANGGUAN KEHAMILAN MENGGUNAKAN METODE F-TOPSIS BERBASIS WEB - Fatmawati, Amelia; Marisa, Fitri (DINAMIKA DOTCOM, 2019)
Pregnancy is a normal function of the body and part of the life phase of women, during this period there is the possibility of pregnant women have a pregnancy disorder. To determine the type of pregnancy disorder the officer has certain patient criteria ie symptoms experienced by the patient. Decision-making issues can be complex because of the inclusion of multiple objectives and criteria. Thus, the method of Fuzzy Technique For Order Preference By Similarity To Ideal Solution (F-TOPSIS) was chosen. Fuzzy logic is a method of problem-solving control system, which is suitable to be implemented on the system, and in TOPSIS method there are alternatives and criteria of data that has been added and can be determined its matching rank. The alternative is used based on 12 types of pregnancy disorders only. While the criteria used to get a matching ranking is based on the symptoms experienced by the patient. In order to produce a suitable output with the data, the officer should enter the symptoms according to the existing pregnancy disorder criteria data. If the officer does not enter the appropriate symptoms, the user should enter at least 2 symptoms that other pregnancy diseases do not have. And if the user only inserts one symptom of the data, then the output does not match the existing data.Keywords: fuzzy, interference, pregnancy, diagnosis, TOPSIS